PENGUATAN INTEGRITAS PANCASILA DAN TOLERANSI BERAGAMA PADA ANAK USIA PENDIDIKAN DASAR - Surmini (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Ngawi, 2024)
ABSTRACT; Integrity is a concrete step in forming a positive personality, one of which is an attitude of honesty. Integrity is needed to strengthen character development based on the values, norms and philosophical meaning of Pancasila as the state ideology. The focus of this research is on steps to emphasize the integrity of Pancasila which is emphasized on children of primary education age who are in the school environment, family environment or community environment. Instilling Pancasila integrity is very important as a way to foster religious tolerance as early as possible in children's interactions with their friends. The formulation of the problem in this research is first, what are the steps to strengthen the integrity of Pancasila in elementary school age children?; secondly, how can the integrity of Pancasila contribute to attitudes of religious tolerance in elementary school age children? The research method uses descriptive qualitative, namely in the form of comprehensive information collection. The results of the research show that the manifestation of an attitude of Pancasila integrity in religious tolerance among children of elementary school age can be done by respecting friends of different religions, working together to maintain the cleanliness of the classroom and the surrounding environment, and helping each other and prioritizing common interests.